Genotyping before azathioprine administration in dermatology. (1st February 2022) - Shipman, K. E.; Shipman, A. R.; Marinaki, A. M.
Abstract: Click https://wileyhealthlearning.com/#/online-courses/7d0b59ae-5b45-4a42-a0a4-d0cea56c92e0 for the corresponding questions to this CME article.